THE IMPORTANCE OF TRANSPORT SYSTEM DEVELOPMENT IN CYPRUS - Parlińska, Maria; Panchenko, Maryna (Acta Scientiarum Polonorum. Oeconomia, 2015)
The purpose of this study is to investigate and assess the economic conditions and policy priorities for Cyprus transport policy. The main aspects of transportation in Cyprus and the relative position of the region as compared to a benchmark (EU countries) are discussed. The main aim is to give a more detailed indication of the strengths and weaknesses of the transport system in the country and to address areas for future intervention. Where relevant this accompanied by recommendations with respect to the overall transport policy of the country.